Seroprevalence of SARS-CoV-2 antibodies among Jordanian citizens: A cross-sectional study of the demographic and clinical factors that ameliorate serum IgG concentration - Walid Abu Rayyan (Journal of Applied Pharmaceutical Science, 2022)
The emergence of a confound virus in China has caused a new pandemic spread worldwide, and the disease was entitled “coronavirus disease-19 (COVID-19).” High incidence rates combined with an exponential increase in mortality numbers among infected persons have been reported by the ministries of health all over the world. Screening of IgG immunoglobulin against severe acute respiratory syndrome coronavirus (SARS-CoV-2) was implemented for the determination of the prevalence and durability of the disease among citizens throughout the pandemic. The objectives of this study were to determine the levels of IgG antibodies against COVID-19 in the serum of Jordanian citizens after the third corona wave and to highlight the correlation between both demographic and clinical factors and the levels of IgG immunoglobulin. A cross-sectional study was conducted between September 2021 and January 2022 including 412 Jordanian citizens. Total IgG antibodies were qualitatively assayed against SARS-CoV-2 using the enzyme-linked immunosorbent assay technique. The median age was 34 years, 59% were male, and 41% were female. The seroprevalence was 81.8% for the study population with a mean of 15.17 IU/ml. 45.4% of the positive participants reported a previous COVID-19 infection, whereas the rest of the study population were subjected to vaccine shots. There was no significant difference in IgG levels when the participants were grouped by gender. IgG antibody levels were significantly lower among smokers and those with O blood groups, whereas levels were higher among participants with the B blood groups or negative Rh groups. Demographic factors including gender, age, education, residence, vaccination, and vaccine type did not influence the immunoglobulin level, whereas smoking and blood group affected the levels negatively.
Keywords: COVID-19, SARS-CoV-2 antibodies, seroprevalence, smoking, Jordan